PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MELALUI MATA KULIAH PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Usman, Usman; Bahraeni, Bahraeni (Inspiratif Pendidikan, 2016)
These research findings describe the implementation and the effectiveness of cooperative learning model in Pancasila and Civic Education course at Tarbiyah and Teaching Science Faculty of UIN Alauddin Makassar. This research was conducted at UIN Alauddin Makassar. The research subjects were the students of Tarbiyah and Teaching Science Faculty who learn Pancasila and Civic Education course. They were the 84 students of Islamic Education Department, class of 5-6 and 7-8 in 2015 period. The class of 5-6 was a class that implemented jigsaw as one of cooperative learning models. It was considered as experimental class of the model. Meanwhile, the class of 7-8 was a class that did not implement the model in which it was only as benchmark class. The data were collected through observations, questionnaires, and tests. The findings showed that the implementation of cooperative learning model in the course was effective. It was supported by the evidence that the average score of the implementation was 4.66. The effectiveness of the implementation of the model was supported by the improvement of students’ learning outcomes in terms of cognitive and attitudes. The results of students’ attitude were from 3.6 (good) to 4.8 (excellent). Meanwhile, the cognitive achievement was from 71.85 (classically complete but 14 students did not complete with the score 50-68) to 80.1 (classically complete but 1 students did not complete individually).